Budget Efficiency Policy and the Violation of the Right to Educational Priority: A Case Study of Instruksi Presiden Nomor 1 Tahun 2025 (Presidential Instruction Number 1 of 2025) - Wilma Silalahi; Gesta Subysesa Maharwani Adeputri (Journal of Human Interaction and Social Studies, 2026)
The issuance of Instruksi Presiden Nomor 1 Tahun 2025 concerning budget efficiency in the implementation of the 2025 State Budget and Regional Budget has generated significant constitutional and administrative law debates in Indonesia. The policy mandates substantial expenditure reductions across ministries and government agencies, including the education sector, despite the constitutional requirement under Article 31 paragraph (4) of the Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 that education receive priority funding. Simultaneously, the government allocated substantial financial resources to the Free Nutritious Meals Program (Program Makan Bergizi Gratis), creating concerns regarding the consistency of fiscal priorities and the protection of constitutional rights. This study employs a normative legal research method using statute, conceptual, and case approaches. Primary legal materials consist of constitutional and statutory provisions, while secondary materials include scholarly literature and legal doctrines. The findings indicate that the implementation of budget efficiency measures through Instruksi Presiden Nomor 1 Tahun 2025 potentially conflicts with constitutional guarantees of educational rights and exceeds the permissible limits of executive discretion under administrative law principles. The study further emphasizes the need for stronger constitutional oversight and accountability mechanisms to ensure that fiscal policies remain consistent with constitutionally protected educational priorities.